Scattering of electrons in oxygen underdoped YBa₂Cu₃O₇₋x single crystals - Khadzhai, G.Ya.; Vovk, R.V.; Vovk, N.R. (Functional Materials, 2014)
The electrical resistivity in the range of Tc-300 K in the layer planes of YBa₂Cu₃O₇₋x single crystals with a range of oxygen deficiency, which is characterized by the Tc in the range 78 + 92 K was studied. The experimental data on the resistance in normal state are approximated by an expression that takes into account the scattering of electrons on phonons, as well as on defects and the fluctuation conductivity in 3D-model of the Aslamazov-Larkin theory. According to this approximation, depending upon the oxygen deficiency, the Debye temperature changes from 245 to 400 K, coherence length ξc(0) ≈ 0.5 Å .